Evolution of Mesopores in Monolithic Macroporous Ethylene-Bridged Polysilsesquioxane Gels Incorporated with Nonionic Surfactant - Atsushi Mushiake; Kazuyoshi Kanamori; Kazuki Nakanishi (International Journal of Polymer Science)
By combining the micellar templating in nanometer scale with the polymerization-induced phase separation in micrometer scale, ethylene-bridged polysilsesquioxane gels with hierarchical macropores and mesopores are prepared. The difference of mesopore structures depending on the method of the solvent removal has been observed by the X-ray diffraction and the nitrogen adsorption-desorption measurements. During the hydrothermal treatment under the basic condition, the reorganization of the polysilsesquioxane gel network occurred differently depending on the alkoxy group contained in the precursors. From 29Si CP/MAS NMR measurements, it was revealed that the crosslinking density of the hydrothermally treated gels was increased so that the highly ordered mesostructure of the wet gel could be preserved even after the evaporative drying of solvent.